Evolving trends and burden of idiopathic epilepsy among children (0–14 years), 1990–2021: a systematic analysis for the Global Burden of Disease study 2021 - Tu, Fulai; Tu, Zhengcheng; Jiang, Xinrui; Zhao, Meng; Li, Wei; Wu, Chunfeng; Wei, Pingmin (Frontiers in Neurology, 2025)
ObjectiveThis systematic analysis aims to elucidate the trends and burden of idiopathic epilepsy among children aged 0 to 14 from 1990 to 2021, utilizing Global Burden of Disease (GBD) 2021 data to explore demographic and geographical variations, highlight progress, and identify ongoing challenges.MethodsData were sourced from the GBD 2021 database, focusing on children aged 0–14. Annual absolute numbers and age-standardized rates for incidence (ASIR), prevalence (ASPR), mortality (ASMR), and disability-adjusted life years (ASDR) of idiopathic epilepsy were retrieved. Joinpoint regression analyses assessed changes over time, calculating average annual percentage change (AAPC) statistics. Data collation and visualizations were conducted using R software, with statistical significance established at a p-value threshold of 0.05.ResultsIn 2021, there were 1,227,191 incident cases, 6,095,769 prevalent cases, 3,564,497 DALYs, and 18,171 deaths due to idiopathic epilepsy globally. The ASIR increased by 0.27% from 55.74 to 61.35 per 100,000 population from 1990 to 2021. In contrast, ASPR (AAPC = −0.03), ASMR (AAPC = −1.60), and ASDR (AAPC = −1.01) all decreased. Regionally, the low-middle SDI region had the highest burden, while the high SDI region had the highest ASIR and ASPR. The low SDI region experienced the highest ASMR and ASDR. Significant regional variations were noted, with the African Region exhibiting the highest ASIR and ASDR, while the Western Pacific Region had the lowest. Nationally, substantial variations were observed across 204 countries, with notable differences in ASIR, ASPR, ASMR, and ASDR.ConclusionDespite overall declines in ASPR, ASMR, and ASDR, the slight increase in ASIR and regional disparities highlight ongoing challenges. Low and low-middle SDI regions continue to bear a higher burden, underscoring the need for targeted interventions and improved healthcare access. Future efforts should focus on strengthening healthcare systems, enhancing diagnostic and treatment capabilities, and increasing awareness, particularly in resource-limited regions.